Innovation-driven industrial green development: The moderating role of regional factors. (10th June 2019) - Li, Wei; Wang, Jue; Chen, Rongxiao; Xi, Yongqin; Liu, Shi Qiang; Wu, Feimei; Masoud, Mahmoud; Wu, Xueping
Abstract: Industrial green development (IGD) is a critical response to the over-consumption of natural resources and pollution caused by modern industry. Innovation-driven IGD has generated great interest in recent years. However, relatively less attention has been paid to the various aspects of IGD and the moderating role of regional factors, including the developmental stage of IGD, government-scale, and enterprise-scale. The present study was conducted to fill these research gaps using panel data across 30 provinces in China from 2005 to 2015. The empirical results show that 1) innovation does promote IGD and is most effective in low-carbon production, followed by resource reduction, economic operation, and pollution abatement; 2) there is an inverted U-shaped relationship between the regional IGD level and the role of innovation in IGD; and 3) both government-scale and enterprise-scale contribute to the innovation-driven IGD. These findings provide new insights into the impact of innovation on IGD and may shed light on future decisions related to green development. Highlights: Innovation significantly contributes to industrial green development. IGD level shows an inverted U-shaped relation with the role of innovation in IGD. Large-government-scale enhances innovation-driven IGD. Large enterprises have an advantage in promoting innovation-driven IGD.